Two-dimensional materials and their applications in fuel cells - Zeyu Lu; Erbo Zhao; Chao Zhang; Chen Chen (iScience, 2024)
Summary: In recent years, two-dimensional (2D) materials have been extensively studied and applied in the field of catalysis on account of their high specific surface areas, high exposure of metal active sites, and readily tunable structures. This article introduces various 2D materials (including materials composed of a few atomic layers) and the related synthesis methods and discusses their catalytic performances for hydrogen fuel cells, in particular, for oxygen reduction reaction and hydrogen oxidation reaction. At the end of this review, the advantages and current challenges of 2D materials are summarized, and the prospects of 2D electrocatalytic materials are proposed.